Peran Penyuluh Pertanian Dalam Penanggulangan Hama Penyakit Pada Bawang Merah (Allium Cepa L) Di Kampung Arsopura Distrik Skanto Kabupaten Keerom - Kellen, Selmi Yohana Stefanie; Tapyor, Fredrika (Agrotek, 2023)
The agricultural sector is a strategic sector in national development. The increase in production has been given by agricultural extension activities. The agricultural instructor must be someone who is competent in the field of agriculture and can communicate effectively and be responsive in dealing with every problem and question quetioned by farmers. The centers for shallot production in Papua Province are Kerom, Merauke, Tolikara and Jayawijaya Regencies. Shallot farming is always faced with risks. in the form of a decrease in production due to unpredictable weather factors and attacks by pests and diseases (such as wilt disease). To overcome the problems above, an agricultural instructor is needed who can help farmers in diagnosing pests and diseases of shallot plants. The research aims to determine the role of agricultural instructors for shallot farmers in controlling plant pests. This research was carried out in Arsopura village, Skanto District, Keerom Regency for 6 months from August 2022 to February 2023. This research used the Arithmetic Mean analysis method with average assessment criteria of 1.00-1.66 with categories of No Role, 1.67- 2.33. There were 60 questions asked by the resource person for each indicator, with 17 facilitator indicator questions, 15 motivator questions, 14 educator questions and 15 communicator questions. The results of the research show that agricultural extension workers play a role in controlling pests and diseases in shallot plants. The scores obtained for the facilitator indicator were 2.69, motivator 2.69, educator 2.34, and communicator 2.44, each in the Role category. Agricultural instructors play a very important role and always provide new technologies to increase shallot production, in Arsopura Village, Skanto District, Keerom Regency.